Upgrading informal settlements in South Africa: a partnership-based approach - Stewart, Thomas (University of the Free State, 2018)
The upgrading of informal settlements has become one of the most comprehensive, complex, controversial, capital-intensive, and often emotive developmental interventions orchestrated and funded by the South African public sector. Many initiatives, however, happen without there being meaningful collaboration between the various role players. In this publication, some of the ‘cutting-edge’ initiatives and a revisit to proven practices and debates are discussed and generously supported by case studies, experience, evidence, and appropriate examples. This is further enhanced by the collaborative effort of the diversity of authors who have managed to simplify and capture the essence of the subject matter in such a way that it can be applied in the formulation of policy.